PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 2 LUBUKLINGGAU - Erma Fitriyanti Erma Fitriyanti Erma Fitriyanti (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to describe the effect of the Contextual Teaching and Learning model on the learning outcomes of class XI students of SMA Negeri 2 Lubuklinggau. The research method used was pure experiment. Data collection techniques in research using tests. The data analysis technique used the following steps: normality test, homogeneity test, and hypothesis testing. Based on the results of research and discussion, it is known that there is an effect of the Contextual Teaching and Learning learning model on the learning outcomes of class XI students of SMA Negeri 2 Lubuklinggau. 11. After being given treatment by applying the Contextual Teaching and Learning learning model, it is known that the final test result (post-test) of the experimental class is 80.82 greater than the result of the calculation of the final test (post-test) of the control class with an average value of 76, 4. Then the data analysis was carried out using the t-test formula so that the t-test value was 2.112. This result was compared with the t-table at the significant level of 5%, namely: 2.112> 1.671. that there is an effect of the Contextual Teaching and Learningn learning model on the history learning outcomes of class XI students at SMA Negeri 2 Lubuklinggau.